Colorimetric logic response based on aptamer functionalized colloidal crystal hydrogels. Issue 17 (15th April 2015) - Ye, Baofen; Wang, Huan; Ding, Haibo; Zhao, Yuanjin; Pu, Yuepu; Gu, Zhongze
Abstract : A novel colorimetric logic system with visualization output signals was developed in aptamer-cross-linked colloidal crystal hydrogels. Abstract : A novel colorimetric logic system based on the aptamer-cross-linked colloidal crystal hydrogel (CCH) was developed. With the input stimuli of Hg 2+ and Ag +, the CCH displayed shrinking response and colour change corresponding to the logical "OR" and "AND" gate. The visualization of the logic output signals is realized.